Pollen morphology and its relation with meiotic irregularities in ten species of campuloclinium (eupatorieae, asteraceae) - Farco, Gabriela Elizabeth (2017)
Fil: Farco, Gabriela Elizabeth. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.